Bacillus sp. Acting as Dual Role for Corrosion Induction and Corrosion Inhibition with Carbon Steel (CS) - Karn, Santosh K.; Fang, Guan; Duan, Jizhou (Frontiers in Microbiology, 2017)
In the present work we, investigated the role of five different bacteria species as a corrosion inducer as well as corrosion inhibitor with carbon steel (CS). We observed the ability of different bacteria species on the metal surface attachment, biofilm formation and determined peroxidase, catalase enzyme activity in the detached biofilm from the CS surface. Our results clearly showed that each bacteria strain has different behaviour for surface attachment like DS1 3.3, DS2 2.5, DS3 4.3, DS4 4.0 and DS5 4.71 log cfu/cm2 and for biofilm it was about 8.3 log cfu/cm2. The enzyme peroxidase and catalase was found in significant concentration within the biofilm peroxidase and reaches its maximum with DS4 36.0 U/ml while the minimum was 19.54 U/ml in DS3. Meanwhile the catalase has reached the maximum for DS4 and DS5 with 70.14 U/ml while the minimum was 57.2 U/ml for DS2. Furthermore, scanning electron microscopy (SEM) was conducted to observe the biofilm while the electrochemical impedance spectroscopy (EIS) was used to observe corrosion in the presence of bacteria. However electrochemical results clearly confirmed that, the DS1, DS3, DS4 and DS5 strains have statistically significant microbially influenced corrosion (MIC-factors) of 5.46, 8.51, 2.36 and 1.04, while DS2 protective effect factor of 0.89. Weight loss data with carbon steel also favours that corrosion was induced by DS1 and DS3, whereas DS2 and DS5 have no any effect while DS4 strain had very less weight loss and played no role in the corrosion. In the present study, we established the relation of peroxidase enzyme activity of the isolates. DS1 and DS3 and having peroxidase in the range 22.18, 19.54 U/ml which induce the corrosion whereas DS2 and DS5 having 28.57 and 27.0 U/ml has no any effect and DS4 36 U/ml has inhibitory effect, increasing concentration inhibiting the corrosion. For Catalase DS1, DS3 have 67.28, 61.57 U/ml which induce corrosion while DS2 and DS5 57.71 and 59.14 U/ml also has no effect whereas DS4 70.14 U/ml can inhibit corrosion. Overall, our results clearly indicated that in a particular range both enzymes can induce the corrosion. Our objective is to search